Vanek’s tumour: a rare cause of small bowel intussusception - Jain, Meenal; Sundaresan, Vinoth; Gowthaman, Siddhartha; Manickam, Ramanathan (International Surgery Journal, 2021)
Adult intussusceptions which are most always caused by pathological lead points are rare and account for about 1% of all bowel obstructions and 5% of all intussusceptions. Most of them present with acute or chronic non-specific symptoms and due to which its initial diagnosis can sometimes be missed or delayed. We present the case of a 52-year-old lady who presented with intestinal obstruction caused by an ileo-ileal intussusception, caused by a peculiar tumour, inflammatory fibroid polyp (IFP).